Finite element simulation of the thermal conductivity of perforated hollow sphere structures (PHSS): Parametric study - Hosseini, Seyed Mohammad Hossein (Elsevier BV, 2009)

(untitled)
This paper investigates the thermal properties of a new type of hollow sphere structures. For this new type. the sphere shell is perforated by several holes in order to open the inner sphere volume and surface. The effective thermal conductivity of perforated sphere structures in a primitive cubic arrangement is numerically evaluated for different hole diameters and different dimensions of the joining elements.